ANALISIS INDEKS HARGA KONSUMEN SEBAGAI INDIKATOR TINGKAT INFLASI DAN HUBUNGANNYA DENGAN TINGKAT PENGANGGURAN TERBUKA - YULIUS KURNIA SUSANTO (Media Bisnis, 2013)
Consumer Price Index (CPI) is one of the economic indicators that provide information on the prices of goods and services paid by consumers. CPI is an indicator of the rate of inflation. Surakarta CPI in April 2012 amounted to 121.53 while the CPI Tarakan 153.41 which is the lowest value and the highest of 66 major cities in Indonesia in April 2012. With the fulfillment of goods and services in the town of Surakarta and the active role of the Government of Surakarta city to monitor the prices of goods and services consumed by the public, causing the prices of goods and services are relatively stable and tends to fall. With the problem of flooding, electricity and water as well as meeting the needs of goods and services consumed from external Tarakan, hence causing the supply of goods and services decreased. This can cause the price of goods and services consumed by the public to be more expensive and tend to rise. The high aggregate supply and aggregate demand constant then inflation low. The high aggregate supply will increase the real output, ie full employment and unemployment down. And vice versa, the low aggregate supply and aggregate demand constant then inflation high. The low aggregate supply will reduce the real output that is labor and unemployment rise.